Conflict and Democratic Preferences - Nicole Stoelinga; Tuuli Tähtinen (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We investigate how exposure to conflict events shapes individuals' democratic preferences, focusing on support for democracy in general and perceptions of governance within one's own country. We examine how ethnic affiliation–whether an individual belongs to an ethnic group with access to state power–influences democratic attitudes, reflecting differences in social standing and expectations about democratization. Using a rich data set covering more than 30 African countries over two decades, we exploit variation in the timing of conflict events relative to survey interviews to identify causal effects. Our findings show that conflict exposure, on average, increases support for democracy, but the effects vary by ethnicity and regime type. In autocracies, conflict triggers rally-around-the-flag effects: support for democracy rises, but so do perceptions of the state. Violence also increases trust in ruling institutions in autocratic regimes, an effect that is absent in more democratic settings.
Keywords: D74; 330; democracy; political preferences; conflict; protest; trust